Porokeratosis of Mibelli - literature review and a case report - Flávia Regina Ferreira; Leopoldo Duailibe Nogueira Santos; Fernando Augusto Nogueira Mendes Tagliarini; Marcia Lanzoni de Alvarenga Lira (Anais Brasileiros de Dermatologia, 2013)
Porokeratosis is a disorder of epidermal keratinization characterized by annular plaques with an atrophic center and hyperkeratotic edges, and includes a heterogeneous group of disorders that are mostly inherited in an autosomal dominant form. This report describes a 5 year-old female patient, with porokeratosis of Mibelli confirmed histopathologically. The rarity of this disorder, its clinical exuberance and the destructive character of the lesions, as well as the facial and mucosal involvements, unusual in this form of porokeratosis, and also its onset in early childhood motivated this report.